1998
DOI: 10.1128/jcm.36.3.756-763.1998
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Non-O1, Non-O139 Vibrio cholerae Associated with an Unusual Upsurge in the Incidence of Cholera-Like Disease in Calcutta, India

Abstract: There was an inexplicable upsurge in the incidence of non-O1, non-O139 Vibrio cholerae among hospitalized patients admitted to the Infectious Diseases Hospital, Calcutta, India, between February and March 1996. Of the 18 strains of V. cholerae isolated during this period, 15 belonged to the non-O1, non-O139 serogroups (4 belonged to O144, 3 belonged to O11, 1 each belonged to O6, O8, O12, O19, O39, and O58, and 2 strains could not be typed), 2 belonged to the O139 serogroup, and 1 belonged to the O1 serogroup.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 33 publications
3
55
1
Order By: Relevance
“…V. cholerae non-Ol, non-0139 strains, on the other hand, rarely express TCP or contain the tcpA gene (9). Interestingly, Sharma et al described as enteropathogenic V. cholerae (EPVC), serogroups of non-O 1, non-0139 V. cholerae that do not possess the CTX genetic element but that can cause diarrhea in humans by an unknown mechanism (32).…”
mentioning
confidence: 99%
“…V. cholerae non-Ol, non-0139 strains, on the other hand, rarely express TCP or contain the tcpA gene (9). Interestingly, Sharma et al described as enteropathogenic V. cholerae (EPVC), serogroups of non-O 1, non-0139 V. cholerae that do not possess the CTX genetic element but that can cause diarrhea in humans by an unknown mechanism (32).…”
mentioning
confidence: 99%
“…Our previous studies have shown that the amount of NMDCY produced by strains of V. cholerae vary widely [15]. Therefore, it appears that strains of V. cholerae which produce NMDCY above a certain amount are capable of inducing diarrhea which might explain why certain strains of V. cholerae non-O1 non-O139 devoid of CT are associated with sporadic diarrhea [12,34]. One means to assess the contribution of NMDCY to the secretory response induced by bacterial cells would be to compare a mutant devoid of NMDCY and such a mutant is currently being constructed.…”
Section: Resultsmentioning
confidence: 99%
“…Vibrio cholerae O1 or O139 can be detected rapidly using probes or primers that use the rfb region responsible for O-antigen biosynthesis (Albert et al, 1997;Hoshino et al, 1998). This might not be the case for non-O1, non-O139 strains diagnosed as the causative agent of diarrhea cases in the Indian subcontinent and elsewhere (Bagachi et al, 1993;Dalsgaard et al, 1995;Rudra et al, 1996;Sharma et al, 1998). From a diagnostic point of view, toxigenicpathogenic and nontoxigenic-nonpathogenic strains of V. cholerae can be differentiated by the presence of CT and the toxin coregulated pilus genes.…”
Section: Introductionmentioning
confidence: 99%